Linking defects, hierarchical porosity generation and desalination performance in metal–organic frameworks. Issue 14 (12th March 2018) - Liang, Weibin; Li, Lin; Hou, Jingwei; Shepherd, Nicholas D.; Bennett, Thomas D.; D'Alessandro, Deanna M.; Chen, Vicki
Abstract : The composite membranes with defective metal–organic frameworks (MOFs) show a significant increase in water flux, without compromising the high salt rejection. Abstract : Composite membranes with defective metal–organic frameworks (MOFs) connect the emerging fields of MOF topological modification, MOF-polymer interfacial engineering and composite material functionalization. Although defective MOFs can be fabricated via thermal or chemical treatment, the relationship between hierarchical MOF structure and their performance in a polymeric membrane matrix has so far not been investigated. Here we show how a modulator fumarate-based MIL-53(Al) microwave synthesis process results in defective MOFs. This ligand replacement process leads to materials with hierarchical porosity, which creates a higher mesopore volume and Brønsted acidity without compromising the crystalline structure and pH stability. Compared with stoichiometric ratios, increasing the reaction time leads to more effective defect generation. The subsequent incorporation of defective MOFs into polyvinyl alcohol pervaporation membranes can effectively promote the fresh water productivity in concentrated brine treatment, with salt rejection of >99.999%. The membranes also have good long-term operational stability with effective antifouling behavior. We provide evidence that topological engineering of the MOF surface is related to their physical and chemical behaviors in a polymeric matrix, opening up the possibility of MOF defect engineering to realize selective separations, catalysis and sensing within a polymeric matrix.